2021
DOI: 10.1111/nph.17247
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to two heatwave intensities in a Mediterranean citrus orchard are identified by combining measurements of fluorescence and carbonyl sulfide (COS) and CO2 uptake

Abstract: Summary The impact of extreme climate episodes such as heatwaves on plants physiological functioning and survival may depend on the event intensity, which requires quantification. We unraveled the distinct impacts of intense (HW) and intermediate (INT) heatwave days on carbon uptake, and the underlying changes in the photosynthetic system, in a Mediterranean citrus orchard using leaf active (pulse amplitude modulation; PAM) and canopy level passive (sun‐induced; SIF) fluorescence measurements, together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 98 publications
(196 reference statements)
0
8
0
Order By: Relevance
“…The simulation of COS uptake is strongly coupled to GPP through g s and V max (which is included in g cos ) and therefore relies on the accuracy of these model parameters. However, several studies have shown that the ratio of COS to CO 2 deposition velocities (in the literature also called "leaf relative uptake") varies with temperature (Cochavi et al, 2021;Stimler et al, 2010) and humidity (Sun et al, 2018b;Kooijmans et al, 2019), in addition to the better known variability with light.…”
Section: Recommendations For Cos-specific Future Model Developmentmentioning
confidence: 99%
“…The simulation of COS uptake is strongly coupled to GPP through g s and V max (which is included in g cos ) and therefore relies on the accuracy of these model parameters. However, several studies have shown that the ratio of COS to CO 2 deposition velocities (in the literature also called "leaf relative uptake") varies with temperature (Cochavi et al, 2021;Stimler et al, 2010) and humidity (Sun et al, 2018b;Kooijmans et al, 2019), in addition to the better known variability with light.…”
Section: Recommendations For Cos-specific Future Model Developmentmentioning
confidence: 99%
“…The modeled COS uptake is strongly coupled to GPP. However, several studies have shown that the ratio of COS to CO2 deposition velocities (in literature also called the leaf relative uptake ratio) varies with temperature (Cochavi et al, 2021;Stimler et al, 2010) and humidity (Sun et al 2018;Kooijmans et al 2019), in addition to the better known variability with light. The temperature response of the COS uptake is currently taken from Vmax and is scaled with an empirical temperature function (Eq.…”
Section: Recommendations For Cos-specific Future Model Developmentmentioning
confidence: 99%
“…(2018) and Cochavi et al. (2021) during heat waves, in a Mediterranean pine forest and citrus orchard, respectively.…”
Section: Conclusion and Outlooksmentioning
confidence: 97%